Nursing Technologies Creativity as an Expression of Caring: A Grounded Theory Study - Kissa Bahari; Anunciacion T. Talosig; Jesus B. Pizarro (SAGE Publishing, 2021)
Caring expression in nursing is rapidly changing to include the use of sophisticated healthcare technologies. Unfortunately, few nurses participate in developing healthcare technologies. The current study aimed to generate a theory of nursing grounded in the phenomenon of nursing technologies creativity in nursing practice. The study design used a constructivist grounded theory. Sixteen Indonesian nurses selected by purposive sampling were interviewed in-depth. Data analysis used constant comparative analysis through Charmaz's coding process. This study generated two core conceptual categories that included technological creativity and drivers for technological development. Five theoretical statements were developed leading to the Technological Creativity as Caring in Nursing Theory. This theory is a middle-range theory that focuses on technological creativity to express caring for patients, nurses, and management in nursing practice.